Purple corn extract alleviates 2,4-dinitrochlorobenzene-induced atopic dermatitis-like phenotypes in BALB/c mice - Huiwon No (Taylor & Francis Group, 2021)
Zea mays L. (Poaceae), also known as purple corn, is an annual herbaceous plant that is grown as food for human consumption in a variety of forms, including cooking oils and sweeteners in processed food and beverage products. The purpose of this study was to determine whether a novel purple corn extract, FB801, might have an anti-atopic dermatitis (AD) effect on AD-like skin lesions induced by 2,4-dinitrochlorobenzene (DNCB) in BALB/c mice. Topical sensitization (1%) and challenge (0.3%) by DNCB were performed on the dorsal skin and right ear of BALB/c mice to induce AD. Following FB801 and dexamethasone administered orally, the severity of skin lesions was examined macroscopically and histologically. Serum levels of immunoglobulin E (IgE) and various cytokines were determined by enzyme-linked immunosorbent assay. Oral administration of FB801 significantly reduced typical symptoms of AD (erythema/bleeding, swelling, molting/erosion and scaling/drying), scratching frequencies, and the recruitment of inflammatory and mast cells. In addition, FB801 suppressed serum levels of IgE and T helper (Th)2 type cytokines such as interleukin (IL)-4 and IL-10 in DNCB-treated BALB/c mice. Furthermore, FB801 reduced the degradation of inhibitor of nuclear factor-κB proteins (NF-κB) in tumor necrosis factor (TNF)-α-stimulated human keratinocyte (HaCaT) cells. These results suggest that FB801 inhibited the development of the AD-like skin symptoms by regulating Th1 and Th2 responses in the skin lesions in mice and suppressing TNF-α induced NF-κB activation in HaCaT cells, suggesting that FB801 has potential application as an effective alternative therapy for the prevention and management of AD.